A New Three-Level Reduced Switch-Count Three-Phase F-type Rectifier and Its Control Without Current Sensing - Komurcugil, Hasan; Güler, Naki; Bagheri, Farzaneh; Bayhan, Sertac (IEEE Computer Society, 2025)
This paper presents a new three-level reduced switch-count three-phase F-type rectifier and its control without current sensing. Unlike the existing three-level three-phase rectifier topologies, which use twelve switching devices, the proposed topology uses only nine switches. This, in turn, reduces costs and enhances reliability. Moreover, the voltage stress on the switching devices is more evenly distributed across the components, leading to the use of lower voltage-rated devices. The control of the proposed rectifier is achieved by a control strategy that eliminates the need for current sensing which reduces control implementation costs. The functionality of the proposed topology and its control method is verified using MATLAB/Simulink simulations under different operating conditions, including steady-state operation, step changes in resistive load, and variations in the reference DC-link voltage. The simulation results verify that the DC-link voltage is effectively controlled, and the total harmonic distortion (THD) of the grid currents remains within the limits defined by international standards. © 2025 IEEE.
51st Annual Conference of the IEEE Industrial Electronics Society, IECON 2025 -- 2025-10-14 through 2025-10-17 -- Madrid -- 215214
Keywords: current sensorless control; F-type rectifier; Multi-level rectifier; reduced-switch count; unity power factor